Edukasi Pengunaan Suplemen Vitamin dan Mineral Dalam Pencegahan Stunting Bagi Masyarakat Desa Sejahtera Sulawesi Tengah - Magfirah, Magfirah; Utami, Indah Kurnia; Marzuki, Sitti Aisyah; Letana, Trace Chintia (Progran Studi Farmasi Universitas Mandala Waluya, 2024)
Stunting is a national health problem that is a global health priority that can affect the quality of human resources (HR) as the future generation of the Indonesian nation. One of the efforts to deal with the stunting problem is to increase communication through community service activities in the form of education about stunting, which is one embodiment of the stunting reduction strategy in accordance with presidential regulation number 72 of 2021 concerning the acceleration of stunting reduction in Indonesia. Sejahtera Village, Palolo District, Sigi Regency, Central Sulawesi was chosen as a place for community service because it is one of the villages with a high incidence of stunting in Sigi Regency. Community service activities aim to invite the community and provide education so that the community can use vitamin and mineral supplements properly and correctly as a step to support government programs in reducing the number of stunting incidents in children with a focus on pregnant women. The method used is socialization by providing counseling using leaflets followed by discussion sessions, question and answer and pretest posttest. PKM activities take place at the Sejahtera Village office and are attended by the local community and village officials to facilitate the running of the activities. As a result of the activity, the community was very enthusiastic and were able to increase their knowledge through the posttest questionnaires that were distributed. From the pretest calculation results, it was 24,95% and the posttest results showed that 65,24 % of the public knew how to prevent stunting. It can be concluded that this PKM activity is very beneficial for the people of Sejahtera Village.